Gut microbiota in health and disease - Shreyashi Ganguly; P Chandrasekhara (Wolters Kluwer Medknow Publications, 2019)
The human intestinal microbiota refers to the total population of micro-organisms that colonise the human intestines. Most organisms in the gut are non-pathogenic and co-inhabit with the host enterocytes in a commensalic and mutualistic relationship. The gut commensals aid in nutrient metabolism, xenobiotic and drug metabolism, antimicrobial protection, immunomodulation and maintenance of the integrity of the gut barrier and structure of the gastro-intestinal tract. Dysbiosis of these organisms have been implicated in the pathogenesis of several diseases. The advent of culture independent techniques has enabled the identification and phylogenetic classification of these organisms. These study methods include gene sequencing by high-throughput amplicon pyrosequencing (16sRNA for bacteria, accuracy 99.9%). Microbiota composition is affected by the mode of delivery, antibiotics usage during pregnancy, preterm labour, diet in infancy, environment & lifestyle, geographical locations, individual host genetics, in adults ageing & diet. The dominant phyla (in a state of normal health) are Firmiculates (51%), Bacetroidetes (41%), Proteo bacteria (5%), Actinobacteria (1.8%) and Verrucomicrobia (1.2%). Most abundant fungi are Ascomycota and Microsporidia. The degree of archaeal diversity in the gut microbiota of healthy individuals appears to be low. The two genera Methanobrevibacter and Nitrososphaera appear to be mutually exclusive. Bacteriophages are the most predominant organism in the human gut microbiome. Role of gut microbiome is implicated in several diseases, which range from inflammatory bowel diseases to cancer, all the way to alzheimers. The understanding and recognition of various gut-microbiome axes has enabled elucidation of novel pathologic pathway that are ripe for therapeutic manipulation. Prebiotics and probiotics aid in the recolonization of the gut with normal "health-promoting-good" bacteria. Other therapeutic approaches are faecal microbial transplantation, which is being employed in clostridium difficile infection, and inflammatory bowel diseases. Their role and benefits in other diseases are emerging every day.